PENERAPAN PROGRAM EMPLOYEE RELATIONS DALAM MENINGKATKAN MOTIVASI KERJA KARYAWAN DI PT. PLN (PERSERO) PUSLITBANG - Risma Kartika; Arwidia Anindito (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2017)
Building on the success of a company requires a good Implementation of the program so that the external and internal public can continue to be faithful and loyal. Implementation of the program provide motivation for employees is one of the important role that can produce maximum performance of the employees so that led to the attainment of the objectives of a company. Employees are assets in the company so that communication with them is an important thing to do. Communication needs to be woven and well managed because communication can be directed to achieve the desired goals of the company. In order to improve moral can not be separated from the responsibility of the company to carry out goal-directed communication motivate employees. Communicate to motivate can be realized in the form of employee relations activities. PT PLN (Persero) PUSLITBANG as one branch of a foreign policy that is engaged in services that have public relations (PR), activities related to developing relationships with employee relations are handled by the part. Used literature review includes a number of concepts concerning the application of employee relations, and employee motivation. This study used qualitative methods. This is a descriptive-qualitatif study. Based on the findings, PR PT PLN (Persero) PUSLITBANG not apply four overall implementation proces. But employee relations activities have been very well built. It can be seen from the many programs that have been conceived and developed by internal parties, so as to support employee motivation which can produce a productivity.